2016
DOI: 10.1248/bpb.b16-00078
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Tetrachloride-Induced Nephrotoxicity in Mice Is Prevented by Pretreatment with Zinc Sulfate

Abstract: Carbon tetrachloride (CCl4) is commonly used as a chemical inducer of experimental liver injury. In addition, many studies showed that CCl4 can induce kidney damage. In the current study, we evaluated the protective effect of zinc (Zn) against CCl4-induced nephrotoxicity. We hypothesized that this protective effect would result from the ability of Zn to serve as an inducer of metallothionein (MT), a known endogenous scavenger of free radicals. We administered Zn (as ZnSO4) 50 mg/kg subcutaneously once daily fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 30 publications
3
28
0
Order By: Relevance
“…Total malondialdehyde (MDA) levels were estimated by a colorimetric microplate assay (Oxford Biochemical Research, Oxford, MI, USA) according to the manufacturer's protocol and as previously described (Yoshioka et al, 2016a(Yoshioka et al, , 2016b.…”
Section: Measurement Of Malondialdehyde Levels and Total Antioxidant mentioning
confidence: 99%
“…Total malondialdehyde (MDA) levels were estimated by a colorimetric microplate assay (Oxford Biochemical Research, Oxford, MI, USA) according to the manufacturer's protocol and as previously described (Yoshioka et al, 2016a(Yoshioka et al, , 2016b.…”
Section: Measurement Of Malondialdehyde Levels and Total Antioxidant mentioning
confidence: 99%
“…15,16) In addition, Anjiki et al reported JTX induced MT in the liver and small intestines. 13) Our current study demonstrate i.p.…”
Section: +mentioning
confidence: 99%
“…In addition, not only APAP but also other hepatic injury chemicals such as Cd and bromobenzene reportedly show hepatoprotective effects by pretreatment with Zn or using MT-KO mice [28][29][30]. We also reported that Zn-induced MT expression has a protective effect against CCl 4 -induced hepato-and nephrotoxicity [17,18]. Our current study demonstrates that i.p.…”
Section: Resultsmentioning
confidence: 58%
“…Total malondialdehyde (MDA) levels in the liver were examined with a colorimetric TBARS microplate assay kit (FR40; Oxford Biochemical Research, Oxford, MI, USA) in accordance with the manufacturer's protocol and as previously described [18].…”
Section: Measurement Of Malondialdehyde Levels In Livermentioning
confidence: 99%